2000
DOI: 10.1073/pnas.97.14.7882
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin 3 induces the reversion of melanocytes to glia through a neural crest-derived glial-melanocytic progenitor

Abstract: Functional signaling of endothelin 3 (ET3) and its receptor B (ETRB)has been shown to be required for the development of neural crest (NC)-derived pigment cells in mouse, but the precise role of ET3 is not completely understood. Using the avian embryo as a model, we previously reported that ET3 promotes the survival and proliferation of unipotent melanocyte and bipotent glia-melanocyte precursors in trunk NC cultures. Here we investigated whether, at later stages, embryonic pigment cells respond to ET3. Such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 35 publications
6
139
0
3
Order By: Relevance
“…Such dependency is consistent with our findings (26) that GM precursors of trunk origin are a privileged target for the survival-and proliferation-promoting effects of ET3 in vitro. The strong potential of ET3 to trigger expansion of GM stem cells may also underlie the capacity of differentiated glial cells and melanocytes to reverse their phenotypic program and transdifferentiate reciprocally in vitro (36,37,53). GM cells isolated from the cephalic NC showed a delayed response to ET3 because they were unaffected by treatment during the first cloning.…”
Section: Discussionmentioning
confidence: 99%
“…Such dependency is consistent with our findings (26) that GM precursors of trunk origin are a privileged target for the survival-and proliferation-promoting effects of ET3 in vitro. The strong potential of ET3 to trigger expansion of GM stem cells may also underlie the capacity of differentiated glial cells and melanocytes to reverse their phenotypic program and transdifferentiate reciprocally in vitro (36,37,53). GM cells isolated from the cephalic NC showed a delayed response to ET3 because they were unaffected by treatment during the first cloning.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies using quail and mouse embryos have reported that EDN3 affects the melanocyte lineage population by increasing their number in a dose-dependent manner (Lahav et al 1996(Lahav et al , 1998Reid et al 1996;Opdecamp et al 1998;Dupin et al 2000). In addition, exogenous overexpression of EDN3 driven by keratin 5 in transgenic mouse embryos induced proliferation of melanocyte precursors and led to hyperpigmentation on most areas of their skin (Garcia et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma and nevus cells can exhibit such phenotypic changes in vivo (53,54). The inducible transdifferentiation of the F10.9 cells may recapitulate molecular switches that operate when neural crest-derived progenitors develop into either melanocytic or glial lineages (55,56) and may help identify them. We investigated here mechanisms involved in the transcriptional activation of promoters from two myelin genes, Po and MBP.…”
Section: Discussionmentioning
confidence: 99%